A Study on Solar Irradiance and Lux Illuminance: Conversion Guide - Michael, Peter R.; Johnston, Danvers E.; Moreno, Wilfrido (Innovations in Science and Technology Vol. 4, 2022)
This study establishes a conversion standard between solar irradiance and lux illuminance. With this conversion, a solar researcher can utilize a low-cost light meter to measure solar irradiance light spectra. The standard for measuring solar irradiance utilizes the units of watts per meter squared (W/m2). Irradiance meters are both costly and limited in the ability to measure low irradiance values. With a lower cost and higher sensitivity in low light conditions, light meters measure luminous flux per unit area (illuminance) utilizing the units of lumens per meter squared or lux (lx). An effective conversion factor between W/m2 and lx would enable the use of light meters to evaluate photovoltaic performance under low solar irradiance conditions. A survey of the literature found no definitive and readily available "rule of thumb" conversion standard between solar irradiance and illuminance. Easy-to-find Internet sources contain conflicting and widely varying values ranging from 688449 to 21000 lx for 1000 W/m2 (1 Sun) of solar irradiance. Peer-reviewed literature contains Luminous Efficacy equivalent values ranging from 21 to 131 lx per W/m2. This manuscript explores the relationship and establishes a theoretical and laboratory measurement guide for converting solar irradiance and illuminance. The conversion factor includes standards data, equipment calibration accuracy, and uncertainty estimates. Solar Irradiance of 1 Sun (1000 W/m2) for an LED-based solar simulator is (116 ± 3) klx and (122 ± 1) klx for outdoor sunlight.